IMPACTOS DA ADOÇÃO DE PROCEDIMENTOS PARA CONTRATAÇÕES DE SERVIÇOS PÚBLICOS - Novelli, Gabriela Repke (2021)
The public procurement market is the largest business sector in the world. It represents approximately one fifth of world production. In Brazil, it is mostly regulated by the General Bidding Law (Law n°. 8.666/1993) which is complemented by other laws, decrees and related normative instructions. In recent years, several regulations have introduced innovations and standards to the bidding model. Given this changing scenario, it is necessary to rethink and adapt the public procurement processes. In this context, the main objective of this research was to analyze the impacts of adopting procedures for contracting public services in the Bidding Coordination of the federal university of Espírito Santo. To achieve the proposed objective, business process management techniques were applied, using improvement tools. As for the methods, a multi-method approach was used with an emphasis on action research and with the formation of Focus Groups for analysis, diagnosis and validation of the actions. The dysfunctions of the sector chosen to be the focus of this study were identified and improvements were proposed. The modeling of the service processes of the Bidding Coordination was carried out and afterwards the impacts of the implementation of the procedures were analyzed. The results of the impact analysis showed that the procurement coordination services' contracting processes became more effective, transparent and standardized. As a technical product, it was possible to create conclusive technical reports in the format of (one) ordinance and manuals with guidelines for contracting services.